Cytochrome P450 Genetic Variations Can Predict mRNA Expression, Cyclophosphamide 4‐Hydroxylation, and Treatment Outcomes in Chinese Patients With Non‐Hodgkin's Lymphoma. (9th February 2017) - Shu, Wenying; Chen, Lingyan; Hu, Xiaoye; Zhang, Meimei; Chen, Wensheng; Ma, Lei; Liu, Xiaoyan; Huang, Jianing; Pang, Tingyuan; Li, Jia; Zhang, Yu
Abstract: To investigate the impact of cytochrome P450 (CYP) genetic polymorphisms CYP2B6, CYP2C19, and CYP3A5 on mRNA expression, cyclophosphamide/4‐hydroxycyclophosphamide pharmacokinetics, and treatment outcomes of the R‐CHOP regimen (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) in Chinese patients with non‐Hodgkin's lymphoma, 567 cases were investigated. Plasma concentrations of cyclophosphamide/4‐hydroxycyclophosphamide were determined using liquid chromatography–tandem mass spectrometry and pharmacokinetic parameters calculated. The frequencies of CYP2B6*1/*29 and CYP2B6*1/*30 were 18 (3.2%) and 30 (5.3%), respectively. Liver samples with CYP2B6*29/*30, CYP2C19*2, CYP2B6*6, or CYP3A5*3 had significantly lower target mRNA expression. Samples with CYP2B6*6 and/or CYP2C19*2 had lower exposure to 4‐hydroxycyclophosphamide, whereas those with CYP2B6*1G/*1H had higher exposure. Multivariate model showed that samples with CYP2C19*2 or CYP2B6 785A>raG had worse treatment response than samples with CYP3A5*3 . CYP2C19*2, CYP2B6*6, CYP2B6*29, and CYP2B6*30 were protective factors for toxicity in the multivariate model. The best model for gene–gene interactions for treatment response contained CYP2C19*2, CYP2B6 785A>G, and CYP3A5*3 (cross‐validation consistency [CVC], 8/10; P = .0035). The best prediction model for grade 2–4 toxicities had CYP2C19*2, CYP2B6 785A>G, and 516 G>T (CVC, 10/10; P < .0001). In previous reports, we were the first to report that the frequency of copy‐number variations in CYP2B6 is higher among Chinese than among other ethnic populations. Genetic variations in CYP2B6, CYP2C19, and CYP3A5 dramatically affected the mRNA expression of proteins, the pharmacokinetics of 4‐hydroxycyclophosphamide, and the R‐CHOP treatment response in Chinese subjects. Patients carrying CYP3A5*3 were more likely to have a better treatment response, whereas patients with CYP2C19*2 or CYP2B6 516G>T, or CYP2B6 785A>G had higher tolerance to treatment.